Stem cell therapy in Alzheimer’s disease: current status and perspectives - Ou, Chu-Min; Xue, Wei-Wei; Liu, Dong; Ma, Liya; Xie, Hai-Tao; Ning, Ke (Frontiers in Neuroscience, 2024)
An incurable neurogenerative illness, Alzheimer’s disease, is the cause of most global health, medical, and social disasters. The two main symptoms are cognitive impairment and neuronal loss. Current medications that target tau protein tangles and Aβ plaques are not very effective because they only slow the symptoms of AD and do not repair damaged cells. Stem cell-based treatments, however, present an alternative strategy in the treatment of AD. They have the capacity to divide into specialized adult cells, have self-renewal abilities, and multiplication. Stem cells can now be employed as a donor source for cell therapy due to developments in stem cell technology. This review covers preclinical and clinical updates on studies based on targeting the tau protein tangles and Aβ plaque, as well as four types of stem cells employed in AD treatment. The review also outlines the two basic pathologic aspects, tau protein tangles and Aβ plaques, of AD.